Effectiveness Of Loving Massage To Treat Back Pain In Pregnant Women In Third Trimester - Ika Mardiyanti; Ratna Ariesta Dwi Andriani; Rizki Amalia (Universitas STRADA Indonesia, 2021)
This study used an analytic design with a cross sectional design with a Quasi Experiment approach to Non Equivalent Control Group Design. Samples were taken using a total sampling of 30 pregnant women, 15 received intervention and 15 controls. Data analysis using Mc Nemar and Mann Withney statistical test. The results showed that (66.7%) of respondents were of low risk age (20-35 years), (83.3%), (70%) of low risk parity (children <5). Statistical analysis with Mc Nemar obtained = 0.01 < = 0.05 meaning that there is an effect of loving massage on back pain, and from the results of Mann Withney obtained = 0.007 <α = 0.05 meaning that there is a difference between the intervention group and the control group . The conclusion is that there is an effect of giving loving massage to back pain in third trimester pregnant women